Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.biochi.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Binding site of MraZ transcription factor in Mollicutes

Abstract: Mollicutes (mycoplasmas) feature a significant loss of known regulators of gene expression. Here, we identified the recognition site of the MraZ-family regulator of Mycoplasma gallisepticum, which is conserved in many species of different clades within class Mollicutes. The MraZ binding site is AAAGTG[T/G], in the promoter of mraZ gene it forms a series of direct repeats with a structure (AAAGTG[T/G]N3)k, where k = 3 most frequently. MraZ binds to a single repeat as an octamer complex. MraZ can also bind a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…The two others most likely control important but as yet unknown functions. The binding sites of HrcA (Chang et al, 2008) and MraZ (Fisunov et al, 2016) in Mollicutes are known and are highly conserved. The binding site of the YebC/PmpR-family TF was found in A. laidlawii and controls inorganic pyrophosphatase and genes with unknown function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two others most likely control important but as yet unknown functions. The binding sites of HrcA (Chang et al, 2008) and MraZ (Fisunov et al, 2016) in Mollicutes are known and are highly conserved. The binding site of the YebC/PmpR-family TF was found in A. laidlawii and controls inorganic pyrophosphatase and genes with unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…MraZ is conserved in spiroplasmas and mycoplasmas, whereas WhiA is conserved in all Mollicutes. The role of MraZ is more or less known (Fisunov et al, 2016) and appears to be widespread in Bacteria (Eraso et al, 2014); the function of WhiA as a cell division regulator was demonstrated only for Streptomyces coelicolor (Jakimowicz et al, 2006). In this bacterium, the WhiA-family TF was shown to regulate parAB and ftsZ genes.…”
Section: Discussionmentioning
confidence: 99%
“…gallisepticum adaptation to various exposures using non-targeted mutagenesis of genes responsible for terpenoid synthesis in M . gallisepticum 38 . Mutant M .…”
Section: Discussionmentioning
confidence: 99%
“…Cloning and purification procedures were performed as described in [ 12 ]. The HsdC (GCW_02350) coding sequence was amplified from the genomic DNA of M. gallisepticum S6 (forward primer: ATTAGGATCC ATGTTTGATTATGCAAAGAAAATTA, reverse primer: TATAGTCGAC ATCATCTAATTTCATGCCAATCT, sequences for cloning are underlined).…”
Section: Methodsmentioning
confidence: 99%
“…The HsdC (GCW_02350) coding sequence was amplified from the genomic DNA of M. gallisepticum S6 (forward primer: ATTAGGATCC ATGTTTGATTATGCAAAGAAAATTA, reverse primer: TATAGTCGAC ATCATCTAATTTCATGCCAATCT, sequences for cloning are underlined). The amplicon was cloned into the pETm plasmid with C-terminal His-tag as described previously [ 12 ]. HsdC protein was produced in E. coli BL21-Gold (DE3) cells.…”
Section: Methodsmentioning
confidence: 99%